Selective removal of hidden caries in permanent molars: a clinical and radiographic analysis: Case Report - Vieira, Pedro Henrique Acioly Guedes Peixoto; Regis, Wanessa Fernandes Matias; Praciano, Davi Costa Melo; Marinho, Isabelle Montenegro Alves; de Castro, Raquel Moreira Veiga; Rodrigues, Lidiany Karla Azevedo (Journal of Health & Biological Sciences, 2024)
Background: Hidden caries is characterized by lesions that cannot be detected exclusively through clinical examination, requiring the use of radiographic examinations for their identification. Case Report: This case study presents the management of two lower molars with microcavitations and enamel shading. Additionally, the presence of a pigmented occlusodistal fissure in one of the elements is noted. The radiographic examination revealed an extensive carious lesion in the dentin, which was not in proximity to the pulp and did not exhibit any periapical lesions. This finding led to the diagnosis of hidden caries. The technique of selective removal of the carious tissue was chosen due to its depth and the potential risk of pulp exposure. Then, the dentin/pulp complex was protected, and the definitive restoration was performed. Conclusion: The progression of hidden carious lesions can lead to tooth destruction without visible clinical signs. Treatment should adhere to minimally invasive dentistry principles to preserve tooth structure and reduce the risk of pulp exposure.